Exploitation of the Host Ubiquitin System: Means by Legionella pneumophila - Luo, Jingjing; Wang, Lidong; Song, Lei; Luo, Zhao-Qing (Frontiers in Microbiology, 2021)
Ubiquitination is a commonly used post-translational modification (PTM) in eukaryotic cells, which regulates a wide variety of cellular processes, including differentiation, apoptosis, cell cycle, and immunity. Because of its essential role in immunity, the ubiquitin network is a common target of infectious agents, which have evolved various effective strategies to hijack and co-opt ubiquitin signaling for their benefit. The intracellular pathogen Legionella pneumophila represents one such example; it utilizes a large cohort of virulence factors called effectors to modulate diverse cellular processes, resulting in the formation a compartment called the Legionella-containing vacuole (LCV) that supports its replication. Many of these effectors function to re-orchestrate ubiquitin signaling with distinct biochemical activities. In this review, we highlight recent progress in the mechanism of action of L. pneumophila effectors involved in ubiquitination and discuss their roles in our understanding of bacterial virulence and host cell biology.